Trends and Disparities in the Incidence of Intraocular Foreign Bodies 1990–2019: A Global Analysis - Yuan, Minjie; Lu, Qianyi (Frontiers in Public Health, 2022)
Objectives: This study aims to provide trends and disparities in the incidence of intraocular foreign bodies (IOFBs) from 1990 to 2019 in 204 countries by region, country, socio-demographic index (SDI), age, and sex. Methods: The global, regional and national number of incident cases as well as age-standardized incidence rate (ASIR) of IOFBs were attained from the Global Burden of Disease Study 2019 (GBD 2019). To estimate the trend of ASIR of IOFBs, the estimated annual percentage change (EAPC) was calculated from 1990 to 2019. Results: Globally, although ASIR of IOFBs decreased with an EAPC of -0.93% (95% uncertainty interval [UI] -1.1 to -0.76) from 1990 to 2019, ASIR of IOFBs increased from 2008 to 2019. From 35.79 million (95% UI 23.62 to 50.89) in 1990 to 46.63 million (95% UI 32.45 to 64.45) in 2019, the number of IOFB incident cases worldwide increased by 30.29% (95% UI 19.63 to 43.55). The incidence of IOFBs varied by region and country, and it was closely related to socio-economic development. Furthermore, while ASIR of IOFBs was high in the young population aged 15-49 years, we observed a significant increase in the number of IOFB incident cases in older adults when compared to other age groups. In terms of sex, males accounted for the vast majority of IOFB incident cases. Conclusions: The global ASIR of IOFBs is on the rise, with an increase in incident cases, designating IOFBs as a global health challenge. The incidence of IOFBs cases is directly related to geographic location, socio-economic status, age, sex, and other factors. Our findings could be useful for the control and prevention of IOFBs.